2023
DOI: 10.3390/life13051200
|View full text |Cite
|
Sign up to set email alerts
|

Association of Genetic and Allelic Variants of Von Willebrand Factor (VWF), Glutathione S-Transferase and Tumor Necrosis Factor Alpha with Ischemic Stroke Susceptibility and Progression in the Saudi Population

Mohammed M. Jalal,
Rashid Mir,
Abdullah Hamadi
et al.

Abstract: Stroke is a key cerebrovascular disease and important cause of death and disability worldwide, including in the kingdom of Saudi Arabia (KSA). It has a large economic burden and serious socioeconomic impacts on patients, their families and the community. The incidence of ischemic stroke is probably increased by the interaction of GSTT1 and GSTM1 null genotypes with high blood pressure, diabetes and cigarette smoking. The roles of VWF, GSTs and TNF-alpha gene variations in the induction of stroke are still unce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…The traditional risk factors for T2D include a sedentary lifestyle, obesity, poor diet, smoking, gestational diabetes mellitus, and genetic risk factors [ 8 ]. Genome-wide association studies (GWAs) have demonstrated the link between certain loci and diseases such as cancer, DM, CVD, and others [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The traditional risk factors for T2D include a sedentary lifestyle, obesity, poor diet, smoking, gestational diabetes mellitus, and genetic risk factors [ 8 ]. Genome-wide association studies (GWAs) have demonstrated the link between certain loci and diseases such as cancer, DM, CVD, and others [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%